Natural dyeing of wool and hair with indigo carmine (C.I. Natural Blue 2), a renewable resource based blue dye - Sunsanee Komboonchoo (2018)
Indigo carmine can be used as a source of blue dye for wool and hair dyeing. The option to use indigo carmine in combination with other natural dyes in a one-bath procedure as a hybrid dyeing concept is of interest both for natural dyeing and for coloration of hair. The present study shows that indigo carmine dyeing on wool exhibits the substantial sorption in the range of pH 4-5 and temperature between 40 and 60 °C. Experiments with human hair samples indicate that the experiments on wool can serve as a model that can be applied for hair dyeing. Comparisons of the energy, water and chemical consumption between two-bath dyeing with indigo and natural dyes separately and a one-bath dyeing using indigo carmine together with other natural dyes demonstrates the advantages of the one-bath hybrid dyeing concept. © 2009 Elsevier Ltd. All rights reserved.